'IT'S ALL A QUESTION OF BUSINESS': INVESTMENT IDENTITIES, NETWORKS AND DECISION‐MAKING IN THE CLEANTECH ECONOMY. Issue 3 (September 2014) - Georgeson, Lucien; Caprotti, Federico; Bailey, Ian
ABSTRACT Cleantech has emerged in the last decade as a major new investment sector at the forefront of the green economy. It responds to the need for innovative technologies to combat the impact of global environmental, climate and resource trends. Focusing on the cleantech sector, this article explores the central importance of relationality within the financial domain of the green economy. The central aim of this article is to deepen understandings of the operation of cleantech investment by examining the decision‐making processes of cleantech actors, how these are influenced by (and influence) cleantech investment networks, and the relationships between these factors and the macro‐level drivers and discourses focused on the cleantech sector. A relational economic geography approach is used in conjunction with other frameworks (spanning the cultural, structural and actor‐network dimensions of cleantech investment) to investigate: how cleantech investors define the sector; the macro‐ and micro‐level drivers of cleantech investment; and how cleantech networks form and operate to create and disseminate cleantech discourses and to generate the mutual trust and information sharing needed to secure cleantech investments. In so doing, the article seeks to shed greater light on the micro‐level processes contributing to the creation and growth of cleantech investment markets as an essential catalyst and component of the green economy.